Sudden Appearance of Indurated Erythematous Plaques on a Man’s Face - A. Carter; K. Viswanathan; K. Shulman (Case Reports in Dermatological Medicine)
Rosacea fulminans (RF), previously known as pyoderma faciale, is a rare presentation of rosacea mostly seen in young women. RF is seen very rarely in men. We present below a case of a fifty-year-old male who presented with RF and was successfully treated with a combination of corticosteroids and isotretinoin.